A mobile app for postoperative wound care after arthroplasty: Ease of use and perceived usefulness. (September 2019) - Scheper, H.; Derogee, R.; Mahdad, R.; van der Wal, R.J.P.; Nelissen, R.G.H.H.; Visser, L.G.; de Boer, M.G.J.
Abstract: Background: Early postoperative discharge after joint arthroplasty may lead to decreased wound monitoring. A mobile woundcare app with an integrated algorithm to detect complications may lead to improved monitoring and earlier treatment of complications. In this study, the ease of use and perceived usefulness of such a mobile app was investigated. Objective: Primary objective was to investigate the ease of use and perceived usefulness of using a woundcare app. Secondary objectives were the number of alerts created, the amount of days the app was actually used and patient-reported wound infection. Methods: Patients that received a joint arthroplasty were enrolled in a prospective cohort study. During 30 postoperative days, patients scored their surgical wound by daily answering of questions in the app. An inbuilt algorithm advised patients to contact their treating physician if needed. On day 15 and day 30, additional questionnaires in the app investigated ease of use and perceived usefulness. Results: Sixty-nine patients were included. Median age was 68 years. Forty-one patients (59.4%) used the app until day 30. Mean grade for ease of use (on a Likert-scale of 1–5) were 4.2 on day 15 and 4.2 on day 30; grades for perceived usefulness were 4.1 on day 15 and 4.0 on day 30. Out of 1317 days of app use, an alert was sent to patients on 29 days (2.2%). Concordance between patient-reported outcome and physician-reported outcome was 80%. Conclusions: Introduction of a woundcare app with an alert communication on possible wound problems resulted in a high perceived usefulness and ease of use. Future studies will focus on validation of the algorithm and the association between postoperative wound leakage and the incidence of prosthetic joint infection.